"We're Human Too": Media Coverage of Simone Biles's Mental Health Disclosure during the 2020 Tokyo Olympics. (September 2022) - Thompson, Kevin G.; Carter, Gilbert; Lee, Edwin S.; Alshamrani, Talal; Billings, Andrew C.
When gymnast Simone Biles withdrew from several events at the 2020 Tokyo Olympics due to concern for her mental health, media organizations discussed both her departure and return to competition. Utilizing framing theory, 192 domestic and international news sources published from July to August 2021 were thematically analyzed to examine how media covered Biles's exit and ultimate return to competition. Results show media covered Biles overwhelmingly positively while focusing on her mental health, productivity as an individual and team athlete, heroism, and gender. More specifically, themes of Biles's gender and race were commonly paired with the theme of heroism. Results also indicate domestic news sources were much more likely to mention Biles's race than international news sources. This work adds to growing scholarship about media coverage of high-profile athletes' mental health disclosures.